Desarrollo del pensamiento crítico a través de estrategias mediadas por TIC en Educación Superior. (2016)
This research has the purpose of analyze the contribution of the ICT in the development of the levels of critical thinking of the students of higher education of Atlántico University and CUC University. In this project, we are going to talk about the theoretical framework related with the critical thinking mediated by the ICT during the teaching-learning process in higher education; also, we present the institutional experience with two interest groups of the universities mentioned before. This experience was framed in a descriptive-explanatory investigation, because it describes the way that the ICT can affect the development of the levels of critical thinking and the way that it is provided by the interpretation and the analysis of the results, the progress and difficulties submitted by the students, regarding said levels, once applied the ICT in the teaching-learning process. The collection techniques of information applied, determined that there is a significant contribution of the ICT in the development and strengthening of the critical thinking of the students, supported by the appropriation that the teachers have of them. The content of this investigation project, sum it that the ICT, have been quickly incorporated to the Universities, that is why we consider analyze they contribution in the development and strengthening of the levels of critical thinking in the students.